Association of systemic immune-inflammation index (SII) with risk of psoriasis: a cross-sectional analysis of National Health and Nutrition Examination Survey 2011–2014 - Xuan Yang; Yuxin Pan; Yang Zhang; Yang Meng; Tang Tong; Mingyi Zhao (European Journal of Medical Research)
Abstract Background The systemic immune-inflammation index (SII) is an emerging marker of inflammation, and the onset of psoriasis is associated with inflammation. The aim of our study was to investigate the potential impact of SII on the incidence rate of adult psoriasis. Methods We conducted a cross-sectional study based on the National Health and Nutrition Examination Survey (NHANES) 2011–2014 data sets. Multiple logistic regression analyses with appropriate covariates adjustment were the major methods in this study. Subgroup analyses were conducted by age, gender, race, smoking status, alcohol consumption, history of heart attack, stroke, coronary heart disease and diabetes. Interactions among these variables were also detected. We further utilized smooth curve fitting to explore potential nonlinear associations between SII and psoriasis across different subgroups. The receiver operating characteristic curve analysis was used to assess the diagnostic value of SII for psoriasis in the general population and diabetic individuals. Multiple imputation was adopted as sensitivity analysis to address potential bias due to missing data. Results 9314 participants (≥ 20 years) were included. A significant positive association was observed between SII and psoriasis (OR = 1.56; P = 0.0069). Subgroup analysis revealed significant positive association in males (OR = 1.52; P = 0.0288), females (OR = 1.61; P = 0.0322), Non-Hispanic Whites (OR = 1.55; P = 0.0190), people aged 40–59 years (OR = 1.98; P = 0.0386), diabetics (OR = 3.40; P = 0.0088), and overweight participants (OR = 1.80; P = 0.0034). SII had a higher predictive value for psoriasis in diabetic patients (AUC = 0.62; 95% CI [0.55, 0.70]). In stroke patients, SII was negatively correlated with the occurrence of psoriasis, and interaction test suggested the effect of SII on psoriasis was significantly modified by stroke (P = 0.0003). Nonlinear relationships between SII and psoriasis were observed in participants aged 20 to 39, former smokers, current drinkers, individuals with or without heart attack, those without coronary heart disease, and overweight participants. Conclusions SII was positively associated with psoriasis. Testing for SII levels may help to identify the onset of psoriasis early.